First total synthesis of ampullosine, a unique isoquinoline alkaloid isolated from Sepedonium ampullosporum, and of the related permethylampullosine - Vargas, Didier F. (2019)
Fil: Fil: Vargas, Didier F. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Química Rosario (IQUIR -CONICET); Argentina.